2021
DOI: 10.21475/ajcs.21.15.06.p3171
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of pea (Pisum sativum L.) genotypes to iron deficiency in relation to the growth, rhizosphere acidification and ferric chelate reductase activities

Abstract: Calcareous soils are known problematic lands for agricultural systems because of the low availability of nutrients, particularly iron (Fe). The so-called strategy I plant (e. g. Pea, Pisum sativum L.) which groups dicotyledons and monocots other than grasses, developed root membrane activities that contribute to the improvement of Fe availability. Among the functions considered to be a critical phase in iron absorption is rhizosphere acidification by H-ATPase and Fe(III) reduced by Fe(III) chelate reducctase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…In agreement with our results, several studies showed that subjecting plants to direct Fe deficiency leads to a significant reduction of plant growth and chlorophyll accumulation (Ellsworth et al, 1997 ; Thoiron et al, 1997 ). Krouma ( 2021 ) showed in pea plants that the first consequence of a limited iron availability is the lack of chlorophyll, then young leaves yellowing. Karimi and Salimi ( 2021 ) demonstrated that the leaf chlorosis, electrolyte leakage, Mg and Ca increased significantly when plants are subjected to10 mM sodium bicarbonate, against a drastic decrease of leaf SPAD, N, K, active Fe, total Fe and Zn concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, several studies showed that subjecting plants to direct Fe deficiency leads to a significant reduction of plant growth and chlorophyll accumulation (Ellsworth et al, 1997 ; Thoiron et al, 1997 ). Krouma ( 2021 ) showed in pea plants that the first consequence of a limited iron availability is the lack of chlorophyll, then young leaves yellowing. Karimi and Salimi ( 2021 ) demonstrated that the leaf chlorosis, electrolyte leakage, Mg and Ca increased significantly when plants are subjected to10 mM sodium bicarbonate, against a drastic decrease of leaf SPAD, N, K, active Fe, total Fe and Zn concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The primary symptom is interveinal chlorosis, the development of a yellow leaf with a network of dark green veins. It affects many agricultural crops in the calcareous soils of Tunisia [1]. In these soils having bicarbonate, high pH, and ferric form of iron, Fe deficiency is a major nutritional disorder for plants [1].…”
Section: Introductionmentioning
confidence: 99%
“…It affects many agricultural crops in the calcareous soils of Tunisia [1]. In these soils having bicarbonate, high pH, and ferric form of iron, Fe deficiency is a major nutritional disorder for plants [1]. These physicochemical conditions of soil affect the bioavailability of Fe and hamper plant growth and yield through the inhibition of Fe-dependent functions such as chlorophyll biosynthesis, photosynthesis, respiration, and protein formation [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations